Pengaruh Pemahaman Investasi, Penggunaan Teknologi Media Sosial Dan Hubungan Pertemanan Terhadap Minat Investasi Generasi Milenial Di Pasar Modal - Putu Yolan Mahendrayani; Lucy Sri Musmini (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the effect of understanding investment, use of social media technology and friendship relationships on millennial generation's investment interest in the capital market. This research is a quantitative research. The sample used was 240 respondents with a sampling technique in the form of purposive sampling. In this study, the data used are primary data, namely questionnaires measured using a Likert scale and analyzed using multiple linear analysis with SPSS version 23.0 program. The results show that (1) understanding of investment has an insignificant negative effect on millennial generation's investment interest in the capital market, (2) the use of social media technology has a significant positive effect on millennial generation's investment interest in the capital market and (3) friendship has a significant positive effect on millennial generation's interest in investing in the capital market.Keywords: : Understanding of investment, Use of Social Media, Friendship Relation, investment interest